1992
DOI: 10.1002/bjs.1800791105
|View full text |Cite
|
Sign up to set email alerts
|

Nasogastric intubation and elective abdominal surgery

Abstract: The use of nasogastric tubes after elective abdominal surgery remains standard practice for many surgeons. Such tubes, however, cause much discomfort and are associated with significant morbidity. This paper reviews the arguments for and against nasogastric intubation, and finds little evidence to support its continued routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 37 publications
2
40
0
2
Order By: Relevance
“…Moreover, a nasogastric tube itself may induce vomiting and is associated with several complications (more than 20 % in our study), such as nasopharyngeal soreness, otitis, sinusitis, oesophagitis, digestive bleeding, and intestinal fluid loss [15,16]. In addition, the discomfort caused by a nasogastric tube is one of the most unpleasant aspects of the postoperative course [17].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, a nasogastric tube itself may induce vomiting and is associated with several complications (more than 20 % in our study), such as nasopharyngeal soreness, otitis, sinusitis, oesophagitis, digestive bleeding, and intestinal fluid loss [15,16]. In addition, the discomfort caused by a nasogastric tube is one of the most unpleasant aspects of the postoperative course [17].…”
Section: Discussionmentioning
confidence: 68%
“…Peritoneal contamination, systemic ailments and electrolyte imbalances. Moreover neither is there substantial period of small gut paralysis after surgery nor does intubation effectively decompress it, on the other hand it may even promote ileus [6]. Moss demonstrated the ineffectiveness of gastric aspiration and recommended immediate post operative elemental feeding [15,16].…”
Section: Mjafi Vol 56 No I 2000mentioning
confidence: 99%
“…Studies have demonstrated satisfactory result without routine use in upper and lower abdominal operations [4,5]. Prophylactic intubation can not only cause complications but may even promote ileus [6]. However, despite lack of a rational basis, nasogastric intubation is commonly practised in abdominal surgery.…”
mentioning
confidence: 99%
“…1,2 But prolonged nasogastric intubation is associated with complications like basal atelectasis due to poor cough reflex, aspiration pneumonia, nasal septum necrosis and loss of electrolytes. So now reserved solely for a specific indications.…”
Section: Introductionmentioning
confidence: 99%